Honey Production by a farmer - Singh, Y P; Kaur, Arvinder; Chauhan, S V S (Indian Farming, 2015)
District Morena in Madhya Pradesh is well-known for rapeseed- mustard cultivation, milk and honey production. Out of total 2.68 lakh ha area under cultivation, the net sown area under rapeseed-mustard and berseem is about 1.52 lakh ha; the region is enriched with abundant rapeseed-mustard and berseem flora during the months of October to March. Floras of these crops provide nectar and pollen to honey bees for food and abundant production of honey. Cultivation of these crops and favourable environmental conditions act as a catalyst to start and also support commercial beekeepers from Rajasthan, Uttar Pradesh and Bihar for migratory beekeeping.